bikin jurnal Peningkatan Kemiskinan Akibat Pengangguran Yang Terjadi Di Masa Pandemi Covid-19 Di Kota Bandung - Ariman, Albyn (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2022)
This research was conducted with the aim of providing a description of how the symptoms that occurred during the covid 19 period and the impacts resulting from the effects of covid 19. In conducting the research, the researchers used library research and content analysis techniques. The results of the study show that poverty due to the effects that occurred in the city of Bandung has increased, calculated from BPS data for 2019-2021 from the figure of 3.38 percent, which has increased to 4.37 percent in the city of Bandung. The solution for overcoming poverty due to symptoms is by (1) education and training for jobs according to available fields and employment opportunities. (2) required workplace (3) increase in capital and labor (4) Able to accommodate unemployed workers. (5) can make the industry work